SimplifyingY + -9 = 4(x + -2)
Reorder the terms:-9 + Y = 4(x + -2)
Reorder the terms:-9 + Y = 4(-2 + x)-9 + Y = (-2 * 4 + x * 4)-9 + Y = (-8 + 4x)
Solving-9 + Y = -8 + 4x
Solving for variable 'Y'.
Move all terms containing Y to the left, all other terms to the right.
Add '9' to each side of the equation.-9 + 9 + Y = -8 + 9 + 4x
Combine like terms: -9 + 9 = 00 + Y = -8 + 9 + 4xY = -8 + 9 + 4x
Combine like terms: -8 + 9 = 1Y = 1 + 4x
SimplifyingY = 1 + 4x
Step-by-step explanation:
Find out how much you get money from the annual interest:
100% = 1750
1% = 1750 ÷ 100 = 17.5
6.05% = 17.5 x 6.05 = 105.87
Find out how much you get from interest in 2 years.
105.87 x 2 = 211.74
(Final answer)
Having sex is way better at burning calories, but 11x